Development of Animation Video-Based Learning Media Using Animaker for Grade VII Informatics Subject - Aulia, Nasyadila; Fitri, Sulidar; Muhammad, Taofik (Design Journal, 2026)
This study aimed to develop and assess the feasibility of Animaker-based animated video learning media for Grade VII Informatics, specifically addressing hardware material. The research adopted a Research and Development (R&D) approach utilizing the ADDIE model—encompassing Analysis, Design, Development, Implementation, and Evaluation stages. Twenty seventh-grade students at MTs Mathlabussa'adah participated in the study. Both material and media experts validated the developed learning media, while student feedback was gathered through questionnaires using Likert scale assessments. Material expert validation achieved 92% (highly feasible), whereas media expert validation attained 80% (feasible). Student responses yielded 86.3%, classified as excellent. The high validation scores were attributed to clear material presentation, attractive visual design, appropriate language use, and suitable video duration aligned with student concentration capacity. The findings demonstrate that Animaker-based animated video learning media proves appropriate for Informatics instruction, particularly regarding hardware topics, offering an effective alternative to conventional teaching methods such as textbooks and worksheets.